BIOGAS SYNTHESIS OF COW DUNG WASTE THROUGH FERMENTATION TIME VARIATION PROCESS - Siti Khairani Sinaga, Siti Khairani; Masthura; Lubis, Ridwan Yusuf (EINSTEIN (e-Journal), 2025)
Biogas is a gas that arises when organic materials, such as animal waste, human waste, or garbage, are soaked in water and stored in a closed or anaerobic place (without oxygen from the air). The purpose of this study was to determine the pH value, temperature, methane content, flame length and fire color in biogas made from cow dung waste. This study used 3 variations of fermentation time, namely 14 days, 21 days and 28 days. Based on the results of the study, it is known that the best fermentation time variation is on day 28 with 63% methane content, pH value 7, temperature 280C, flame duration 41 seconds and reddish yellow flame color.